Correlates of genetic monogamy in socially monogamous mammals: insights from Azara’s owl monkeys - Huck, Maren (2014)
Understanding the evolution of mating systems, a central topic in evolutionary biology for more than 50 years, requires examining the genetic consequences of mating and the relationships between social systems and mating systems. Among pair-living mammals, where genetic monogamy is extremely rare, the extent of extra-group paternity rates has been associated with male participation in infant care, strength of the pair bond and length of the breeding season. This study evaluated the relationship between two of those factors and the genetic mating system of socially monogamous mammals, testing predictions that male care and strength of pair bond would be negatively correlated with rates of extra-pair paternity (EPP). Autosomal microsatellite analyses provide evidence for genetic monogamy in a pair-living primate with bi-parental care, the Azara’s owl monkey (Aotus azarae). A phylogenetically corrected generalized least square analysis was used to relate male care and strength of the pair bond to their genetic mating system (i.e. proportions of EPP) in 15 socially monogamous mammalian species. The intensity of male care was correlated with EPP rates in mammals, while strength of pair bond failed to reach statistical significance. Our analyses show that, once social monogamy has evolved, paternal care, and potentially also close bonds, may facilitate the evolution of genetic monogamy.